0016 Educators' Experiences Of Interprofessional Simulations In The Context Of Teaching Undergraduate Health Care Students. (1st November 2014) - Thomas, Susan; Clarke, Christine
Abstract : This study explored the experiences of educators invloved in interprofessional simulations across 3 institutions in the West Midlands. All had been involved in facilitating interprofessional simulations with undergraduate students from medicine, nursing, radiography, physiotherapy and pharmacy. A grounded theory appraoch was used and 10 educators were interviewed. These semi-structured interviews were analysed in conjunction with a review of the current literature. Coding was used to determine the main themes from the respondents' interviews. Educators acknowledged the challenges associated with this form of teaching. Main themes that emerged included the need for preparation and training, the skills and attitudes of differing professional groups, team facilitation and professional identity accompanied by the complex issues of group dynamics and professional tensions. Educators were overwhelmingly suportive of interprofessional simulation as a learning methodology but it was acknowledged that for these initiatives to have the required student outcomes and ultimately improve patient care, educators need to be supported and prepared in their role to develop a colaborative approach to teaching. There is a rapidly expanding requirement for educators to implement interprofessional simulations and this small study lays the foundations to encourage self and peer assessment of facilitation skills utilising published facilitaotr assessment scales and video technology to observe facilitation. The requirement for educators to be fully prepared prior to embarking on such initiative is imperative. References: Anderson ES, CoxD, Thorpe LN. Preparation of educators invloved in interprofessional education. Journal of Interprofessional Care 2009;23(1):81–94 Reeves S, Van Schaik S. Simulation: A panacea for interprofessional learning? Journal of Interprofessional Care 2012;(26):167–169